Atomically dispersed hybrid nickel-iridium sites for photoelectrocatalysis. Issue 1 (December 2017) - Cui, Chunhua; Heggen, Marc; Zabka, Wolf-Dietrich; Cui, Wei; Osterwalder, Jürg; Probst, Benjamin; Alberto, Roger
Abstract Atomically dispersed supported catalysts can maximize atom efficiency and minimize cost. In spite of much progress in gas-phase catalysis, applying such catalysts in the field of renewable energy coupled with electrochemistry remains a challenge due to their limited durability in electrolyte. Here, we report a robust and atomically dispersed hybrid catalyst formed in situ on a hematite semiconductor support during photoelectrochemical oxygen evolution by electrostatic adsorption of soluble monomeric [Ir(OH)6 ]2− coupled to positively charged NiOx sites. The alkali-stable [Ir(OH)6 ]2− features synergistically enhanced activity toward water oxidation through NiOx that acts as a "movable bridge" of charge transfer from the hematite surface to the single iridium center. This hybrid catalyst sustains high performance and stability in alkaline electrolyte for >80 h of operation. Our findings provide a promising path for soluble catalysts that are weakly and reversibly bound to semiconductor-supported hole-accumulation inorganic materials under catalytic reaction conditions as hybrid active sites for photoelectrocatalysis. Atomically disperse catalysts can offer promising activity due to the high exposure of active sites. Here, iridium complexes in solution undergo a binding equilibrium with a nickel oxide surface resulting in atomically disperse iridium and high turnover frequencies for oxygen evolution.